Factors Contributing to Students’ Habit in Learning English - Tawali, Tawali; Kamarudin, Kamarudin (Jurnal Ilmiah Mandala Education (JIME), 2021)
This research aimed at finding out Factors Contributing to Students’ Habit in Learning English. The research was descriptive qualitative research. The subject of the study consisted of 25 students taken from five classes at the fifth semester students of FMBM. The instrument that was in the form of questionnaire. The result was analyzed by using Mile and Huberman (1994) theory (data reduction, data display, conclusion drawing and verification). The result found that there were five factors contributing to students’ habit in learning English especially speaking skill at the fifth semester students of FMBM, they were; Performance Conditions, Affective Factors, Listening Ability, Topical Knowledge, and Feedback during Speaking Activities. And the more dominant factor among those factors were; Performance Conditions (20)/90%, Affective Factors (18)/85%, Topical Knowledge (15)/75%, Listening Ability (10)/35%, and Feedback during Speaking Activities (5)/10%.